(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
Rural and urban hospitals must respond differently to crises such as the COVID-19 pandemic, given their unique situations. In this study, we performed a rhetorical analysis of press releases from rural and urban hospitals in Texas to better understand the crisis communication strategies of the two hospital systems. Following previous literature on narrative sensemaking, place-based storytelling, and pre-crisis management, we found that the examined press releases used setting details to ground their health-related information in their specific communities. Such a strategy made the information accessible and attainable, but potentially reinforced place-based tensions and inequalities. Our study has implications for preventative sensemaking research as well as for crisis communicators attempting to better reach specific communities during a long-term, developing crisis.